2015
DOI: 10.2147/opth.s77210
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of rheumatoid arthritis and their correlation with anti-cyclic citrullinated peptide antibodies

Abstract: PurposeTo study the ocular manifestations of rheumatoid arthritis and to correlate the role of anti-cyclic citrullinated peptide antibody (anti-CCP antibody) with the ocular manifestations.MethodsThree-hundred and ninety-two eyes of the 196 rheumatoid arthritis patients who attended the ophthalmology outpatient department underwent a detailed ocular examination using slit lamp biomicroscopy and ophthalmoscopy. The tear function of all the patients was assessed using Schirmer’s test, tear film break-up time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 10 publications
2
27
1
2
Order By: Relevance
“…All of these OMs are both sight-and life-threatening ones because of their association with systemic vasculitis [16]. A risk factor found in this study was ACPA, as reflected by another report that the presence of ACPA was significantly associated with OMs [17] and was the most prevalent biomarker among RA patients [18]. Therefore, ACPA can be both diagnostic and prognostic and can be easily detected before the occurrence of EAMs [19].…”
Section: Discussionsupporting
confidence: 61%
“…All of these OMs are both sight-and life-threatening ones because of their association with systemic vasculitis [16]. A risk factor found in this study was ACPA, as reflected by another report that the presence of ACPA was significantly associated with OMs [17] and was the most prevalent biomarker among RA patients [18]. Therefore, ACPA can be both diagnostic and prognostic and can be easily detected before the occurrence of EAMs [19].…”
Section: Discussionsupporting
confidence: 61%
“…In the last century, anticitrullinated protein antibodies were discovered. However, anticyclic citrullinated peptide antibodies (anti-CCP antibodies) are more sensitive than RF, and they are special markers of systemic involvement in RA [ 50 ]. Compared with RF, anti-CCP appears to be related to increased and worse ocular manifestation in RA [ 51 ].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…RA is mainly considered as a joint disease, but it has the capacity to inflict multiple organs because of the abnormal systemic immune response. About 17.8–47.5% of patients present the extra-articular manifestations [ 12 , 13 ], among which the ocular surface manifestation is the most common [ 14 , 15 ], which seriously affects the quality of life [ 16 ]. Earlier studies have shown that synovitis is the pathological basis for joint injury in RA [ 5 ].…”
Section: Introductionmentioning
confidence: 99%